Badminton robot batting mechanism design and badminton trajectory simulation - Sun, W.; Kong, J.; Wang, X.; Liu, H. (IOP Conf. Series: Materials Science and Engineering, 2019)
In order to achieve the goal of batting the target quickly and accurately. In this paper, a four-bar linkage mechanism was proposed which used for beating the badminton, and designed a portable badminton robot with omni-directional wheel. Firstly, the 3D model of badminton robot is established. Then the kinematics of batting mechanism is analyzed. Next, the collision of badminton ball is simulated by Adams. Finally, the trajectory simulation for badminton by Particle Swarm Optimization, the parameters of mechanism were optimized.